2017
DOI: 10.18632/oncotarget.17288
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary cancer-favoring engineered vaccinia virus for metastatic hepatocellular carcinoma

Abstract: Engineered vaccinia virus-based therapy shows promising results in patients with advanced hepatocellular carcinoma, although a strategic virus design for the metastatic liver and the study of its efficacy in treating the cancer has not been well assessed. In this paper, we proposed a simple and strategic virus design for targeting metastatic hepatocellular carcinoma. We developed an evolutionary cancer-favoring engineered vaccinia virus (CVV, which is produced by repeated selective replication in cancerous tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“… 5 So far, there has been no study to report that oVV was applied to treat AML, although oncolytic virus therapy has been used for the treatment of other cancers. 15 , 16 , 18 , 36 …”
Section: Discussionmentioning
confidence: 99%
“… 5 So far, there has been no study to report that oVV was applied to treat AML, although oncolytic virus therapy has been used for the treatment of other cancers. 15 , 16 , 18 , 36 …”
Section: Discussionmentioning
confidence: 99%
“…In this animal study, the subjects were randomized into sorafenib, CVV, or sorafenib with CVV. Metastatic regions were interestingly rare in the CVV-treated groups (i.e., CVV or sorafenib with CVV) whereas metastatic regions existed in the sorafenib-treated group [46]. JX-594 is a thymidine kinase gene-inactivated oncolytic vaccinia virus engineered for the expression of transgenes encoding human granulocyte-macrophage-colony-stimulating factor (GM-CSF) and β-galactosidase, which increases antitumor immune responses [39,[47][48][49] This virus is safe in humans and extremely toxic to cancer cells.…”
Section: Oncolytic Immunotherapymentioning
confidence: 97%
“…Metastatic regions were fewer in the CVV-treated groups than in the sorafenib-treated group. The result suggested that CVV can be a promising virus targeting metastatic HCC [ 81 ]. JX-594, an engineered vaccinia virus with a mutation in the TK gene, which controls cancer cell-specific replication, and an insertion in the human GM-CSF gene, which increases antitumor immune responses [ 82 ], is stable and safe in humans and extremely toxic to cancer cells.…”
Section: Oncolytic Virotherapymentioning
confidence: 99%